Control Theory-Based Load Balancing for Wireless Sensor Network - Sanqi Zhou; Yinchao Chen (International Journal of Distributed Sensor Networks)
Wireless sensor networks have been widely studied for decades. There are many research areas that have been explored such as service availability and energy efficiency. Load balancing is one of the key techniques which can be used to solve the tradeoff between the both sides. In this paper, we propose a novel real-time load balancing technique which does not require the knowledge of static traffic demands and is based on control theory. We first formulate the packet forwarding problem into a classic control model and then derive the controller model. Then, we propose an algorithm to implement the controller and perform the simulation. The simulation results show that, our algorithm can balance the network traffic in real time and decreases maximum link utilization (MLU) sharply. Our algorithm reduces MLU by 78.4% compared to the shortest path first (SPF) routing and by 53.8% compared to another packet scheduling algorithm which was proposed in a previous work.